USING RASCH ANALYSIS TO EXPLORE WHAT STUDENTS LEARN ABOUT PROBABILITY CONCEPTS - Mahmud, Zamalia; Porter, Anne (Journal on Mathematics Education, 2015)
Students’ understanding of probability concepts have been investigated from various different perspectives. This study was set out to investigate perceived understanding of probability concepts of forty-four students from the STAT131 Understanding Uncertainty and Variation course at the University of Wollongong, NSW. Rasch measurement which is based on a probabilistic model was used to identify concepts that students find easy, moderate and difficult to understand. Data were captured from the e-learning Moodle platform where students provided their responses through an on-line quiz. As illustrated in the Rasch map, 96% of the students could understand about sample space, simple events, mutually exclusive events and tree diagram while 67% of the students found concepts of conditional and independent events rather easy to understand.Keywords: Perceived Understanding, Probability Concepts, Rasch Measurement Model DOI: dx.doi.org/10.22342/jme.61.1